2013
DOI: 10.1007/s00484-012-0630-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation systems on temporal distribution of malaria vectors in semi-arid regions

Abstract: Previous research models have used climate data to explain habitat conditions of Anopheles mosquitoes transmitting malaria parasites. Although they can estimate mosquito populations with sufficient accuracy in many areas, observational data show that there is a tendency to underestimate the active growth and reproduction period of mosquitoes in semi-arid agricultural regions. In this study, a new, modified model that includes irrigation as a factor was developed to predict the active growing period of mosquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a comparison of the two regression models (adults and larvae) and climatic factors, it seems that larvae are more influenced by the presence of vegetation, waste material, water reservoirs and ditches. The presence of floating and terrestrial vegetation, poor environmental sanitation and extensive irrigation activities that create water reservoirs such as ditches are among the major environmental factors for mosquito abundance and their wide distribution in many habitats (Ohta and Kaga, 2014, Alahmed, 2012, Calhoun et al, 2007, Chaikoolvatana et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of the two regression models (adults and larvae) and climatic factors, it seems that larvae are more influenced by the presence of vegetation, waste material, water reservoirs and ditches. The presence of floating and terrestrial vegetation, poor environmental sanitation and extensive irrigation activities that create water reservoirs such as ditches are among the major environmental factors for mosquito abundance and their wide distribution in many habitats (Ohta and Kaga, 2014, Alahmed, 2012, Calhoun et al, 2007, Chaikoolvatana et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Calhoun et al [41] reported a higher number of Culex larvae in oily/rusty water when compared to clean water. Similarly, Ohta and Kaga [42] found that substantial irrigation activities enhance mosquito growth, lengthen mosquito annual growing periods, and raise mosquito maximum generation numbers by altering natural water in their environment. It was also shown that irrigation systems not only aid mosquito growth during dry seasons but also help to stabilize growth during rainy seasons.…”
Section: Discussionmentioning
confidence: 96%
“…It seems that Culex and Anopheles larvae are more influenced by the presence of vegetation, waste material, water reservoirs, and ditches. The presence of floating and terrestrial vegetation, poor environmental sanitation, and extensive irrigation activities that create water reservoirs such as ditches are among the major environmental factors for mosquito abundance and their wide distribution in many habitats [39,41,42,49].…”
Section: Discussionmentioning
confidence: 99%
“…The lag can be attributed to the time for infiltration to occur, runoff to accumulate in low‐lying areas, and the development time for parasite growth. In addition, past observations have proven that irrigation plays the same function as rainfall in providing larval habitats to support vector growth (Herrel et al., 2001 ; Ohta & Kaga, 2014 ). Hence, irrigation in the dry season in our study created a pseudo‐early rainy season, which causes earlier onset of mosquito breeding and an extended malaria transmission.…”
Section: Discussionmentioning
confidence: 99%